2022
DOI: 10.1186/s12877-022-03469-7
|View full text |Cite
|
Sign up to set email alerts
|

Healthy aging index and its link with relative education between individual and neighborhood: a population-based, cohort study

Abstract: Objectives There is increasing recognition of the importance of neighborhood socioeconomic status (SES) for establishing an age-friendly society. Despite the benefits of improved neighborhood SES, little is known about the link of relative education between individuals and neighborhoods with healthy aging. This study aims to construct a healthy aging index (HAI) accounting for indicators’ interlinkages and to test the association of the HAI with relative education between neighborhoods and indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Psychosocial factors, such as wellbeing, depression, and loneliness, are important measures, especially since the COVID-19 pandemic. As these measures are often included in health and retirement studies and are proposed by the WHO for assessment of functional abilities, they can be used in a standardized score of healthy aging ( 5 , 10 , 21 , 24 , 32 35 ). Previous research related to the exploration of the intrinsic capacity factors for the Latvian population also confirms this evidence ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychosocial factors, such as wellbeing, depression, and loneliness, are important measures, especially since the COVID-19 pandemic. As these measures are often included in health and retirement studies and are proposed by the WHO for assessment of functional abilities, they can be used in a standardized score of healthy aging ( 5 , 10 , 21 , 24 , 32 35 ). Previous research related to the exploration of the intrinsic capacity factors for the Latvian population also confirms this evidence ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such domains as vitality, cognition, and psychology are the most commonly used, i.e., 76% of the reviewed studies reported them. Such domains as locomotion and sensory were reported in only 4-5 studies (7,10,(23)(24)(25).…”
Section: On the Theoretical Approach And Practical Usementioning
confidence: 99%
See 1 more Smart Citation